2012
DOI: 10.1016/j.chiabu.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity among maltreated young adolescents

Abstract: Purpose (1) To identify and compare rates of body mass index (BMI) ≥ 85% (overweight/obesity) and BMI ≥ 95% (obesity) in maltreated versus comparison young adolescents; (2) To determine whether demographic/psychological characteristics are related to high BMI; (3) To determine whether type of maltreatment is related to high BMI in maltreated young adolescents. Methods We compared a sample of maltreated young adolescents to a comparison sample of adolescents from the same neighborhood. The maltreated sample (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 47 publications
1
26
1
6
Order By: Relevance
“…Taken together, these data from female macaques suggest that chronic psychosocial stress exposure alters sensitivity to E2 thereby increasing risk for adverse health outcomes in females. It is also important to study these questions throughout development and adulthood, as stress-induced emotional eating occurs in girls [176178], and results in higher rates of obesity [179182], particularly in girls [176178]. Accounting for sex and gonadal hormones in our examination of stress axis function in obesity will offer clarity on the complex relationship, as well as yield novel targets for alleviating the adverse consequences of obesity specifically in females.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data from female macaques suggest that chronic psychosocial stress exposure alters sensitivity to E2 thereby increasing risk for adverse health outcomes in females. It is also important to study these questions throughout development and adulthood, as stress-induced emotional eating occurs in girls [176178], and results in higher rates of obesity [179182], particularly in girls [176178]. Accounting for sex and gonadal hormones in our examination of stress axis function in obesity will offer clarity on the complex relationship, as well as yield novel targets for alleviating the adverse consequences of obesity specifically in females.…”
Section: Discussionmentioning
confidence: 99%
“…For example, results from rodents clearly show that prenatal stress increases risk for obesity later in life (Tamashiro et al, 2009). Although data from humans are limited, emotional eating in children is associated with reports of stress (Mazur et al, 2011) and children from families reporting more distress have higher rates of obesity (Anderson et al, 2012; Anderson and Whitaker, 2011; Gundersen et al, 2011; Koch et al, 2008; Moens et al, 2009), particularly for girls (Noll et al, 2007; Schneiderman et al, 2012; Suglia et al, 2012). Together, these data support the hypothesis that exposure to social stress during development may be an aggravating factor for DIO during childhood (Evans et al, 2012).…”
Section: Gaps In Understanding Feeding Behavior In Nonhuman Primatesmentioning
confidence: 99%
“…The results are conflicting as to the type of disorder -excess weight 15,37 and underweight 38,39 -and in relation to gender 15,38 , type of abuse 39 , and severity of trauma 37 .…”
Section: Discussionmentioning
confidence: 71%
“…Schneiderman et al 38 investigated whether violence is predictive of obesity in adolescents and observed that individuals in early adolescence with a history of abuse showed higher odds of obesity when compared to their non-abused peers. Considering gender in this association, they noted that only adolescent girls that were victims of sexual and physical abuse showed significantly lower odds of obesity as compared to non-abused girls.…”
Section: Discussionmentioning
confidence: 99%